Reframing domestic roles: Language and gender equality in rural communities - Ilahiyah, Ajeng Inayatul; Herlina Dedy Listiani (CV. Yudhistt Fateeh, 2025)
Traditional gender roles are deeply rooted and often reinforced through everyday language, particularly in rural communities in Indonesia. Word choice and phrases such as “husband helping the wife washing the dishes” or “husband helping wife with childcare” imply that children and domestic work are primarily the responsibility of the wife alone, accidentally perpetuating gender inequality. By involving interactive workshops and discussions with both men and women to raise awareness about the impact of language on gender roles in Kendalrejo village-Pemalang Regency, Central Java, this article examines how altering word choice can influence perceptions of gender roles and promote equality in domestic work. Purposive sampling was carried out to ensure diverse representation, and 10 participants were chosen and joined the research intervention using the framework of Participatory Action Research (PAR). The finding of this research portrays a significant shift in perception with increased recognition of men’s role in domestic work for both women and men. This is a part of mainstreaming gender equality by underscoring the importance of word choice in shaping social norms as well as offering a practical approach in rural settings.